Combined impact of UV radiation and nitric acid on high‐density polyethylene containers as a laboratory test. Issue 10 (8th June 2022) - Geburtig, Anja; Wachtendorf, Volker; Falkenhagen, Jana
Abstract: In a laboratory test, transparent high‐density polyethylene (HDPE) jerrycans have been exposed to both UV radiation and 55 wt‐% nitric acid solution at (41 ± 2)°C, for up to 20 days. For comparison, UV radiant exposure (21 days) and nitric acid exposure (up to 6 weeks) were performed separately, at nearly equal temperatures. The damages are compared with FTIR spectroscopy in ATR and HT‐gel permeation chromatography(GPC) on a molecular level and with hydraulic internal pressure testing as a component test. For the used jerrycans, relevant oxidation can only be found after the combined exposure. This is caused by the decomposition of nitric acid into nitrous gases by UV radiation, which is also observed at lower concentrations (28 wt‐%). After 6 days of laboratory exposure, this is rated as critical, which corresponds to about 1/10 year in Central Europe, according to the UV radiant exposure. The gradual increase in oxidative damage shows the reproducibility of the test. Abstract : A laboratory exposure device was used to simulate the damage of a jerrycan by the combined exposure of UV radiation and the filling good. For the HDPE jerrycans used, the combined exposures of UV radiation and nitric acid at (41 ± 2)°C show a uniform increase in oxidation with duration, confirming the reproducibility of the laboratory test. Based on hydraulic internal pressure tests, this oxidation is considered critical from 6 days, corresponding to 1/10 of the annual UV radiant exposure in Central Europe.